Analysis of weld characteristics of micro-plasma arc welding and tungsten inert gas welding of thin stainless steel (304L) sheet. (December 2016) - Batool, Sadaf; Khan, Mushtaq; Jaffery, Syed Husain Imran; Khan, Ashfaq; Mubashar, Aamir; Ali, Liaqat; Khan, Nawar; Anwar, Muhammad Nabeel
This research work focuses on comparison of the weld geometry, distortion, microstructure and mechanical properties of thin SS 304 L sheets (0.8 mm thickness) welded using micro-plasma arc welding and tungsten inert gas welding process. Initial experiments were performed to identify suitable processing parameters for micro-plasma arc welding and tungsten inert gas welding processes. Microstructures of welds were analysed using scanning electron microscopy, X-ray diffraction and energy dispersive spectroscopy. The results indicate that the joint produced by micro-plasma arc welding exhibited higher tensile strength, higher ductility, smaller dendrite size and a narrow heat affected zone. Samples welded by micro-plasma arc welding process had lower distortion as compared to that welded by tungsten inert gas process. Micro-plasma arc welding was shown to be the suitable process for welding of thin 304 L sheets owing to its higher welding speed and better weld properties as compared to the tungsten inert gas welding process.